Eosinophilic Esophagitis: a rapidly emerging disorder (Swiss Medical Weekly, 2012)
Eosinophilic Esophagitis (EoE), first described in the early 1990’s, has rapidly evolved as distinctive chronic inflammatory esophageal disease. The diagnosis is based clinically by the presence of symptoms related to an esophageal dysfunction and histologically by an eosinophil-predominant inflammation once other conditions leading to esophageal eosinophilia are excluded. This striking male-prevalent disease has an increasing incidence and prevalence in the westernised countries. Currently, EoE represents the main cause of dysphagia and bolus impaction in adult patients. Despite the fact that EoE often occurs in atopic patients, the value of allergic testing is still under discussion. Topical corticosteroids lead to a rapid improvement of active EoE clinically and histologically; they are therefore regarded as first-line drug therapy. Elimination diets have similar efficacy as topical corticosteroids, but their long-term use is limited by practical issues. Esophageal dilation of EoE-induced strictures can also be effective in improving symptoms, but this therapy has no effect on the underlying inflammation. Neither the diagnostic nor the long-term therapeutic strategies are yet fully defined.